2022
DOI: 10.1002/ange.202201993
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Near‐Infrared Luminescence in Lanthanide‐Doped Vacancy‐Ordered Double Perovskite Cs2ZrCl6 Phosphors via Te4+ Sensitization

Abstract: All‐inorganic lead‐free perovskite‐derivative metal halides have shown great promise in optoelectronics, however, it remains challenging to realize efficient near‐infrared (NIR) luminescence in these materials. Herein, we report a novel strategy based on Te4+/Ln3+ (Ln=Er, Nd, and Yb) co‐doping to achieve efficient NIR luminescence in vacancy‐ordered double perovskite Cs2ZrCl6 phosphors, which are excitable by a low‐cost near‐ultraviolet light‐emitting diode (LED) chip. Through sensitization by the spin‐orbital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 74 publications
1
12
0
Order By: Relevance
“…Therefore, various lanthanide ions (Ln 3+/2+ : Ce 3+ , Pr 3+ , Nd 3+ , Sm 3+ , Eu 3+ /Eu 2+ , Gd 3+ , Tb 3+ , Dy 3+ , Ho 3+ , Er 3+ , Tm 3+ , Yb 3+ /Yb 2+ , etc.) have been incorporated into perovskites to notably improve their performances and broaden their applications via single-, co-, or tri-doping, respectively (26)(27)(28)(29)(30)(31)(32)(33). Many landmark works have been achieved by the marriage of lanthanide ions with perovskites.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, various lanthanide ions (Ln 3+/2+ : Ce 3+ , Pr 3+ , Nd 3+ , Sm 3+ , Eu 3+ /Eu 2+ , Gd 3+ , Tb 3+ , Dy 3+ , Ho 3+ , Er 3+ , Tm 3+ , Yb 3+ /Yb 2+ , etc.) have been incorporated into perovskites to notably improve their performances and broaden their applications via single-, co-, or tri-doping, respectively (26)(27)(28)(29)(30)(31)(32)(33). Many landmark works have been achieved by the marriage of lanthanide ions with perovskites.…”
Section: Introductionmentioning
confidence: 99%
“…However, by continuously increasing Eu 3+ concentration to 0.8%, the fluorescence lifetime decreased to 7.83 ms owing to the concentration quenching effect. 32 The unified double exponential behavior of the fluorescence lifetime decay curve suggested that the inorganic CdSe/CdS QDs matrix provided a homogenous electronic transition environment for Eu 3+ ions and certified that Eu 3+ ions were incorporated into the CdSe/CdS QDs lattice.…”
Section: Resultsmentioning
confidence: 95%
“…According to the s → p transitions rule of s 2 ions, the transition of 1 S 0 → 3 P 1 (A band) is partially allowed by spin–orbit coupling (SOC) interaction, and 1 S 0 → 3 P 2 (B band) is forbidden. 21,22 However, the previous reports evidenced that doping would alter the SOC effect. 23–25 Moreover, the octahedral distortion induced by doping breaks partially forbidden s → p transitions.…”
Section: Resultsmentioning
confidence: 95%